1991
DOI: 10.1021/es00016a011
|View full text |Cite
|
Sign up to set email alerts
|

Do marine bacteria degrade .alpha.-hexachlorocyclohexane stereoselectively?

Abstract: Acknowledgment in Memorium. This paper is dedicated to Ernie Hughes, who pioneered the scientific development of the NIST gas SRM program, and who contributed so much of his technical knowledge to numerous interactions with experts in the gas analysis field, worldwide. In the present study, Ernie carried out the analyses of the NPL standards and supplied the SRMs that were analyzed by NPL, but passed away before this paper could be written. His unique insight into the requirements for accuracy in gas standards… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
47
1

Year Published

1997
1997
2010
2010

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(49 citation statements)
references
References 0 publications
0
47
1
Order By: Relevance
“…Although these enantiomers exhibit identical basic physical and chemical properties they behave differently when degraded by microbes because enzymes exhibit stereoselectivity (Müller and Kohler, 2004). Accordingly, the racemic (1:1) mixture of α-HCH released into the environment undergoes enantioenrichment when enantioselective processes are considered (microbial breakdown, selective biological uptake, biotransformation and elimination pathways in food webs (Faller et al, 1991;Falconer et al, 1995;Wiberg et al, 2000)). On the other hand, abiotic transformations such as transport, hydrolysis or photolysis are not enantioselective.…”
Section: Résumé [Traduit Par La Rédaction] Nous Présentons Des Faits mentioning
confidence: 99%
“…Although these enantiomers exhibit identical basic physical and chemical properties they behave differently when degraded by microbes because enzymes exhibit stereoselectivity (Müller and Kohler, 2004). Accordingly, the racemic (1:1) mixture of α-HCH released into the environment undergoes enantioenrichment when enantioselective processes are considered (microbial breakdown, selective biological uptake, biotransformation and elimination pathways in food webs (Faller et al, 1991;Falconer et al, 1995;Wiberg et al, 2000)). On the other hand, abiotic transformations such as transport, hydrolysis or photolysis are not enantioselective.…”
Section: Résumé [Traduit Par La Rédaction] Nous Présentons Des Faits mentioning
confidence: 99%
“…These 19 compounds, due to the existence of axial chirality, are called atropisomers (they are given in Table 2). Most of these compounds are introduced in the environment as racemates, but atropisomers have shown different toxicities and metabolic pathways [64]. Although, GC (with ECD or MS detection) has been the most frequently used technique to analyze PCBs congeners and enantiomers, CE has also proven to be effective in this field.…”
Section: Chiral Analysis Of Pcbsmentioning
confidence: 99%
“…In other work, Faller et al 21,22 reported that the (−) enantiomer of ␣-1,2,3,4,5,6-hexachlorocyclohexane (␣-HCH) was more prevalent off of the east British coast, whereas (+) ␣-HCH was more prevalent in the central North Sea. In another example, Garrison et al 23 reported the preferential degradation of S-(−) 2,4-DP in soil, while Ludwig et al 24 reported the preferential degradation of R-(+) 2,4-DP by marine microorganisms.…”
mentioning
confidence: 99%